2003
DOI: 10.1007/s00421-003-0867-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced endothelial activity reflected in cutaneous blood flow oscillations of athletes

Abstract: Functional alterations of vascular endothelial cells may be evaluated by analysing differences in effects of endothelium-dependent [acetylcholine (ACh)] and endothelium-independent [sodium nitroprusside (SNP)] vasodilators. We evaluated whether a dynamic approach using spectral analysis of the blood flow signal, resulting from the cutaneous red cell flux and recorded by the technique of laser Doppler flowmetry (LDF), can detect higher endothelial responsiveness in trained versus less trained individuals. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…Another interesting approach was by Rossi et al: by performing spectral analysis of the LDF signal, they showed an augmented amplitude of the low frequency band presumably reflecting endothelial function in the trained (Rossi et al, 2006). Similar observations were found in the study performed by Kvernmo et al (Kvernmo et al, 2003).…”
Section: Exercise Augments the Endothelium Dependent Vasodilation In supporting
confidence: 57%
See 1 more Smart Citation
“…Another interesting approach was by Rossi et al: by performing spectral analysis of the LDF signal, they showed an augmented amplitude of the low frequency band presumably reflecting endothelial function in the trained (Rossi et al, 2006). Similar observations were found in the study performed by Kvernmo et al (Kvernmo et al, 2003).…”
Section: Exercise Augments the Endothelium Dependent Vasodilation In supporting
confidence: 57%
“…It has been postulated that low frequencies around 0.01 Hz might reflect endothelial function, the frequencies at arround 0.04 Hz might reflect the neurogenic influence on the vessel wall, the ones around 0.1 Hz myogenic activity, whereas oscillations of higher frequencies at around 0.3 Hz and 1 Hz reffer to respiratory and heart beat activity, respectively (Kvandal et al, 2006). This is one of the tools used to assess endothelial function in physiologic (Kvernmo et al, 2003) and pathologic (Rossi et al, 2011) conditions. The most widely used spectral methods are fast Fourier transform, autoregressive modeling and wavelet analysis.…”
Section: Spectral Analysis Of the Ldf Signalmentioning
confidence: 99%
“…Results: In group I there were only 4 patients with pathological finding, and the number increased in group II [5] and group III [11]. In spite of expectations, group IV (MSA) did not have the highest percent of patients with OH.…”
Section: Discussionmentioning
confidence: 97%
“…An overview of recent experiments related to their physiological origin will be presented. The contribution of each of the cardiovascular oscillatory processes can be expected to change with age, after exercise [5] or in diabetes [6], congestive heart failure and acute myocardial infarction. Results of large clinical, multi-center studies will be presented and potentials of the coupled oscillators approach in gaining clinical and physiological insight will be discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation